Mollà Nasreddin the making of a modern trickster (1906-1911) - Afary, Janet; Afary, Kamran (Edinburgh University Press, 2023)
In the early 20th century, a group of artists and intellectuals reinterpreted the Middle Eastern trickster figure Nasreddin in their periodical Molla Nasreddin. They used folklore, visual art and satire to disseminate a consciously radical and social democratic discourse on religion, gender, sexuality and power in Transcaucasia and Iran. The periodical reached tens of thousands of people in the Muslim world, impacting the thinking of a generation. This book explores the milieu in which Molla Nasreddin was born, the way the periodical recreated the trickster trope, and the influence of European graphic artists, especially Francisco Goya, on the journal. It focuses on the most creative period, 1906-11, when the journal reflected the social and political concerns of three major upheavals: the 1905 Russian Revolution, the 1906-1911 Iranian Constitutional Revolution, and the 1908 Young Turk Movement